SUPERVISED PATTERN RECOGNITION OF ARCHERS’ RELATIVE PSYCHOLOGICAL COPING SKILLS AS A COMPONENT FOR A BETTER ARCHERY PERFORMANCE - Mohamad Razali, Abdullah; Hafizan, Juahir; Z., Taha (2018)
The current study explores the most significant psychological skills needed for the accomplishment of high archery scores and determines the discriminating psychological coping skills needed for archery performance. 32 archers completed psychological coping skills inventory before their shooting tests. Multivariate techniques of principal component analysis, hierarchical agglomerative cluster analysis and discriminant analysis were applied. The rotated PCA indicates 3 parameters containing 6 and 3 principal components (Pcs). The first Pcs reveal high loadings from three psychological skills. The second Pcs disclose high loadings from two skills, while the third Pcs demonstrate a high loading from only one skill. HACA classified the archers into two classes viz. High-performance group and low performance group. DA discriminates the classes with an excellent accuracy of 93.55%.